Achieving exceedingly constructional characterization of magnesia-yttria (MgO-Y2O3) nanocomposite obtained via oxalate precursor strategy. (January 2020) - Turky, Ali Omar; Shalan, Ahmed Esmail; Ewais, Emad M.M.; Zhao, Hailei; Bechelany, Mikhael; Rashad, Mohamed M.
Graphical abstract: The transmittance spectra of MgO-Y2 O3 nanocomposite synthesized through oxalate precursor route was increased by increasing of Mg ion concentration. Highlights: MgO-Y2 O3 nanocomposite was synthesized using oxalate precursor method. The morphology of nanocomposite was strongly dependent on the MgO content. The transmittance of the nanocomposite was enhanced with MgO, %. Band gap energy was slightly decreased with increasing MgO ratio. Such nanocomposite can be utilized in different optical applications. Abstract: Magnesium yttrium oxide (MgO-Y2 O3 ) nanocomposites have been purposefully tailored using an oxalate precursor pathway. Commonly, MgO-Y2 O3 nanocomposites possessed a significant technological challenge in electroceramics; particularly remarkable as the anode material for solid oxide fuel cells (SOFC). In this regard, different weight ratios, % of MgO and Y2 O3 including (20:80), (50:50) and (80:20) were fabricated based on oxalic acid as a fuel in acidic medium. Indeed, the impact of the annealing temperature on the phase composition, crystallite size, morphology and optical properties was investigated using X-ray diffraction, field emission electron microscope (FESEM), TEM, FTIR and UV–VIS-NIR spectrophotometer. The FESEM results showed the nanocomposite had a cubic like structure with the fine grain sizes of 0–150 nm because of the rapid solidification. The band gap energy was found to be 4.83, 5.10 and 5.08 eV with increasing the ratio of Mg 2+ ion from 20 to 50 and 80, respectively. Eventually, our currently studies consider to be an important achievement to investigate and recognize the features of the MgO-Y2 O3 system for different applications involving microwave systems, advanced displays (field emission display, plasma display, electroluminescent display), ultra-fast sensors, durable, infrared windows and lasers.